Microsatellite based identification of grapevine cultivars traditional in Hungary and in the Carpathian Basin - Bisztray, Gy. D.; Deák, T.; Eisenheld, C.; Pedryc, A.; Balogh, I.; Regner, F. (International Journal of Horticultural Science, 2005)
Grapevine cultivars and clones traditional in Hungary and in the Carpathian Basin are maintained in the genetic collection of the Corvinus University of Budapest. Mostly ancient varieties and clones were genotyped using microsatellite loci. The investigated 6 loci were sufficient to distinguish all cultivars. Some clones could also be separated based mostly on the variable VVS2 loci. For 17 out of the 31 investigated cultivars this is the first report on characterization of the polymorphism of the allele lengths by microsatellite markers on loci: VVS2, VVMD7, VVMD27, vrZAG62.